Synthesis, Characterization and Determination of Partition Coefficient of Some Triazole Derivatives of Coumarins for Their Antimicrobial Activity - JAYASHREE, B.S.; SAHU, A.R.; SRINIVASA MURTHY, M.; VENUGOPALA, K.N. (Asian Journal of Chemistry, 2010)
The triazolo-thiadiazinyl coumarins have been synthesized by the action of 3-bromoacetyl coumarin and substituted triazoles. The synthesized compounds have been characterized by IR, 1H-NMR and mass spectral analysis. An attempt to determine the hydrophobic parameter (partition coefficient) was also established. All the test compounds were screened for their antimicrobial activity by qualitative and quantitative method.